Hypothyroidism: A Literature Review - Hardiant, Excell Defry; Adidaifa, Muhammad Fikri; Salsabila, Tsania Zulfa; Maulana, Muhammad Rafi; Salsabila, Baiq Ghefira Rojwani Putri; Untari, Lania Pradiva; Suryani, Elsa Indah; Paradiesta, Andi Frieskha Naurah; Savitri, Puti Amelia; Rahmat, Basuki (Jurnal Biologi Tropis, 2025)
Hypothyroidism is a condition in which the thyroid gland is unable to produce enough hormones to meet the body's needs. This condition causes a slowed metabolism, which can lead to various symptoms such as fatigue, weight gain, dry skin, hair loss, constipation, cold intolerance, and facial puffiness. Given the widespread impact of hypothyroidism and the potential for serious complications, special attention is needed for early detection, diagnosis, and effective treatment of hypothyroidism. This literature review was conducted using journal review methods and data searches through sources such as PubMed, Google Scholar, and ScienceDirect. The search used the keywords "hypothyroidism," "hypothyroid," "thyroid gland," and "Hashimoto's thyroiditis." The results of the literature review found that the main cause of hypothyroidism is Hashimoto's thyroiditis, an autoimmune disease in which antibodies attack the thyroid gland. Hypothyroidism is diagnosed by examining elevated TSH and decreased free T4 levels, as well as anti-TPO antibody tests to detect Hashimoto's thyroiditis. Treatment for hypothyroidism generally involves administering levothyroxine, a synthetic thyroid hormone, to replace the deficient hormone and normalize metabolic function. Healthy lifestyle support, such as diet and stress management, is also important to help optimally manage this condition. In conclusion, hypothyroidism is characterized by a decrease in thyroid hormone production and preventive management is pharmacological in the form of levothyroxine, while non-pharmacological management is in the form of regulating food intake.